Dithiolene complexes containing N coordinating groups and corresponding tetrathiafulvalene donors - Rabaça, Sandra; Almeida, Manuel (Coordination chemistry reviews, 2010)
The chemistry of transition metal dithiolene complexes containing N coordinating groups and the corresponding TTF donors, is reviewed starting from the ligand synthesis to the coordination structures where these dithiolene complexes are used as bridging units. The dithiolene ligands containing N coordinating atoms present two coordination poles which can selectively bind different metals and act as bridging units in a variety of coordination architectures. The transition metal dithiolene complexes based on these N containing ligands and the corresponding TTF donors can be themselves regarded as ligands. These can be used to coordinate other metals, potentially leading to a diversity of hetero metallic coordination architectures. With the use of appropriate auxiliary ligands they can lead to discrete metal complexes. In addition they can lead to more extended polymeric structures of different dimensionality such as 1D chains, 2D layers or even 3D polymers can also be obtained.